Competition between Silicifiers and Non-silicifiers in the Past and Present Ocean and Its Evolutionary Impacts - Hendry, Katharine R.; Marron, Alan O.; Vincent, Flora; Conley, Daniel J.; Gehlen, Marion; Ibarbalz, Federico M.; Quéguiner, Bernard; Bowler, Chris (Frontiers in Marine Science, 2018)
Competition is a central part of the evolutionary process, and silicification is no exception: between biomineralized and non-biomineralized organisms, between siliceous and non-siliceous biomineralizing organisms, and between different silicifying groups. Here we discuss evolutionary competition at various scales, and how this has affected biogeochemical cycles of silicon, carbon and other nutrients. Across geological time we examine how fossils, sediments and isotopic geochemistry can provide evidence for the emergence and expansion of silica biomineralization in the ocean, and competition between silicifying organisms for silicic acid. Metagenomic data from marine environments can be used to illustrate evolutionary competition between groups of silicifying and non-silicifying marine organisms. Modern ecosystems also provide examples of arms races between silicifiers as predators and prey, and how silicification can be used to provide a competitive advantage for obtaining resources. Through studying the molecular biology of silicifying and non-silicifying species we can relate how they have responded to the competitive interactions that are observed, and how solutions have evolved through convergent evolutionary dynamics.